Modulation of hepatic perfusion did not improve recovery from hepatic outflow obstruction - J. Arlt; W. Wei; C. Xie; A. Homeyer; U. Settmacher; U. Dahmen; O. Dirsch (BMC, 2017)
Abstract Background Focal hepatic venous outflow obstruction frequently occurs after extended liver resection and leads to a portal hypertension, arterial hypoperfusion and parenchymal necrosis. In this study, we investigated the pharmacological modulation of liver perfusion and hepatic damage in a surgical model of hepatic outflow obstruction after extended liver resection by administration of 5 different drugs in comparison to an operative intervention, splenectomy. Methods Male inbred Lewis rats (Lew/Crl) were subjected to right median hepatic vein ligation + 70% partial hepatectomy. Treatment consisted of a splenectomy or the application of saline, carvedilol or isosorbide-5-mononitrate (ISMN) (5 mg · kg−1 respectively 7,2 mg · kg−1 per gavage 12 h−1). The splenectomy was performed during operation. The effect of the treatments on hepatic hemodynamics were measured in non-operated animals, immediately after operation (n = 4/group) and 24 h after operation (n = 5/group). Assessment of hepatic damage (liver enzymes, histology) and liver cell proliferation (BrdU-immunohistochemistry) was performed 24 h after operation. Furthermore sildenafil (10 μg · kg−1 i.p. 12h−1), terlipressin (0.05 mg · kg−1 i.v. 12 h−1) and octreotide (10 μg · kg−1 s.c. 12 h−1) were investigated regarding their effect on hepatic hemodynamics and hepatic damage 24 h after operation (n = 4/group). Results Carvedilol and ISMN significantly decreased the portal pressure in normal non-operated rats from 11,1 ± 1,1 mmHg (normal rats) to 8,4 ± 0,3 mmHg (carvedilol) respectively 7,4 ± 1,8 mmHg (ISMN). ISMN substantially reduced surgery-induced portal hypertension from 15,4 ± 4,4 mmHg to 9,6 ± 2,3 mmHg. Only splenectomy reduced the portal flow immediately after operation by approximately 25%. No treatment had an immediate effect on the hepatic arterial perfusion. In all treatment groups, portal flow increased by approximately 3-fold within 24 h after operation, whereas hepatic arterial flow decreased substantially. Neither treatment reduced hepatic damage as assessed 24 h after operation. The distribution of proliferating cells appeared very similar in all drug treated groups and the splenectomy group. Conclusion Transient relative reduction of portal pressure did not result in a reduction of hepatic damage. This might be explained by the development of portal hyperperfusion which was accompanied by arterial hypoperfusion.